Improved thermoelectric performance of n-type half-Heusler MCo1-xNixSb (M = Hf, Zr) - He, Ran; Zhu, Hangtian; Sun, Jingying; Mao, Jun; Reith, Heiko; Chen, Shuo; Schierning, Gabi; Nielsch, Kornelius; Ren, Zhifeng (Materials Today Physics, 2017)
The MCoSb-based (M = Hf, Zr) half-Heusler compounds were recognized as a promising p-type thermoelectric (TE) material for more than 2 decades although the base compound is intrinsically n-type. Here we investigate the TE properties of Ni-substituted n-type MCoSb. The anomalous changes of carrier concentration and lattice thermal conductivity with higher amount of Ni indicate the presence of atomic disorder. Peak power factor of ∼33 μW cm−1 K−2 and peak ZT of 0.6 are obtained in ZrCo0.9Ni0.1Sb. Further substitute Zr by Hf suppresses the lattice thermal conductivity and yields a peak ZT exceeding 1 in the composition Zr0.5Hf0.5Co0.9Ni0.1Sb at 1073 K. Thus the MCoSb compounds possess promising TE properties by both n- and p-type doping, which is unique among the half-Heusler based TE materials.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Half-Heusler; n-type; Thermoelectric; ZrCoSb